2014
DOI: 10.1037/a0037301
|View full text |Cite
|
Sign up to set email alerts
|

Age, psychological maturity, and the transition to motherhood among English-speaking Australian women in a metropolitan area.

Abstract: In the context of the trend toward delayed parenthood, this study examines whether older maternal age is associated with greater psychological maturity and whether greater psychological maturity provides any adaptive benefit during the transition to motherhood. A sample of 240 predominantly English-speaking Australian women in a metropolitan area expecting their 1st baby (mean age = 32.81 years; 41% conceived after fertility treatment) completed measures of psychological maturity (hardiness, ego development, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…A previous report (Camberis, McMahon, Gibson, & Boivin ) with a larger sample from which participants in the present study were drawn showed that older maternal age was associated with a latent construct of psychological maturity and that psychological maturity contributed to reports of more optimal adjustment in pregnancy and the early months of motherhood. Maturity was conceptualized as a two‐dimensional construct encompassing indices of adaptive self‐regulation, represented by hardiness (Kobasa, Maddi, & Kahn, ) and ego resiliency (Block & Block, ), and social‐cognitive maturity characterized by ego development (Loevinger, ).…”
Section: Age and Parentingmentioning
confidence: 44%
“…A previous report (Camberis, McMahon, Gibson, & Boivin ) with a larger sample from which participants in the present study were drawn showed that older maternal age was associated with a latent construct of psychological maturity and that psychological maturity contributed to reports of more optimal adjustment in pregnancy and the early months of motherhood. Maturity was conceptualized as a two‐dimensional construct encompassing indices of adaptive self‐regulation, represented by hardiness (Kobasa, Maddi, & Kahn, ) and ego resiliency (Block & Block, ), and social‐cognitive maturity characterized by ego development (Loevinger, ).…”
Section: Age and Parentingmentioning
confidence: 44%
“…Support from extended family decreased with increasing maternal age, but older mothers communicated more with their infants than younger mothers (Bornstein et al, ). In contrast, a study of Australian women in a metropolitan area, reported that maternal psychological maturity, increased with age, and was associated with positive adaptation to parenthood in the early months (Camberis, McMahon, Gibson, & Boivin, ).…”
Section: Discussionmentioning
confidence: 94%
“…There are, however, interesting theoretical arguments for doing statistical analyses on the effect of age on psychosocial functioning. Older maternal age may be conceived of as a proxy for personal maturity (Camberis, McMahon, Gibson, & Boivin, 2014). Personal development and growth bring a multitude of benefits including greater psychological flexibility and personality .…”
mentioning
confidence: 99%